Training motivation as mediator of the relationship between training administration and training transfer - Azman, Ismail; Nurul, Afiqah Foboy; Rizal, Abu Bakar; Norzanah, Mat Nor; Herwina, Rosnan (Penerbit Universiti Kebangsaan Malaysia, 2015)
This study examines the relationship between training administration, training motivation and training transfer. A survey method was employed to gather self-administered questionnaires from employees who work at a military oriented health organization. The outcomes of SmartPLS path model analysis revealed two important fi ndings; fi rstly, the relationship between communication and training motivation is signifi cantly related with training transfer. Secondly, relationship between delivery and training motivation is signifi cantly related with training transfer. The result confi rms that training motivation mediates the relationship between training administration and training transfer in the organizational sample. Further, this study provides discussion, implications and conclusion.